2015
DOI: 10.1007/s11605-015-2767-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Clinical Relevance of Speckle-Type POZ Protein in Human Colorectal Cancer

Abstract: Our results suggest that SPOP plays a pivotal role in colorectal cancer (CRC) through mesenchymal-epithelial transition and MMPs, and it may be a potential therapeutic target in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…In our previous study, we suggested the potential role of SPOP in progression of CRC. 13 However, the underlying mechanism remains unknown. In this study, we revealed that the tumor suppressor gene SPOP was inactivated by DNA methylation of its promoter region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we suggested the potential role of SPOP in progression of CRC. 13 However, the underlying mechanism remains unknown. In this study, we revealed that the tumor suppressor gene SPOP was inactivated by DNA methylation of its promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12 Our previous study revealed that SPOP was significantly downregulated and the repression of SPOP promoted metastasis in colorectal cancer. 13 Notably, systematic whole-genome sequencing demonstrates that the SPOP gene is mutated in 6–15% of human prostate cancer, and functional analyses show that these are all loss-of-function mutations. 14, 15 However, there are only about 2% of colorectal cancers harboring SPOP mutation, which means the aberrant low expression level should account for the repression of SPOP function in colorectal cancer, instead of somatic mutation.…”
mentioning
confidence: 99%
“…Numerous studies have explored the role of SPOP in tumorigenesis and progression in CRC. Frequent downregulation of SPOP was detected in CRC tissues compared with paired adjacent normal tissues at both the mRNA and protein levels, and this downregulation was also significantly related to clinicopathologic parameters such as poor differentiation, distant metastasis, and high TNM stage [29]. Furthermore, a decrease in SPOP expression might serve as a potent predictive factor of poor prognosis for patients with CRC according to Kaplan-Meier survival analysis.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 95%
“…Furthermore, a decrease in SPOP expression might serve as a potent predictive factor of poor prognosis for patients with CRC according to Kaplan-Meier survival analysis. In an in vitro study, overexpression of SPOP dramatically inhibited the proliferation and migration of CRC cells via upregulation of E-cadherin and downregulation of vimentin, MMP2, and MMP7, while this process was reversed by silencing of SPOP [29]. Moreover, one study also found that SPOP ablated MMP2 expression in CRC cells by suppressing the SP1 phosphorylation and nuclear translocation that was involved in the PI3K/Akt signaling pathway [101].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 98%
“…Recent research analysis found that SPOP protein was frequently mutated in some tumours, such as endometrial cancer, lung cancer and prostate cancer . Our previous studies reported that SPOP also had a similar situation in colon cancer, but it was not very clear in GC.…”
Section: Introductionmentioning
confidence: 91%